Validitas E-Modul Fisika SMA Berbasis Inkuiri Terbimbing Terintegrasi Etnosains untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik - Cici Dwi Tisa Haspen; Syafriani Syafriani; Ramli Ramli (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
The creative thingking ability of students in high school is still very low. This is due to the ina dequate use of teaching materials. The teaching used are still using printed modules and do not contains steps in the learning model that direct students to be able to improve their creative thingking skills. One of the solutions to improve student’s creative thinking skill in physics learning is to use –electronic mod- ule (e-module). The e-module which is equipped with a Guided Inquiry Learning Model and Integrat- ed Ethnoscience is a suitable combination to increase creative thinking skills. Through the e-module, students are able to learn independently with the help of ethnoscience in their neighborhood. This study aims to determine the level of validity of the e-module physics based Guided Inquiry Integrated eith Ethnoscience to improve student’s Creative Thinking Skills. The type of research is Research and Development (RnD) with the ADDIE development model. But, in this research is limited to the devel- opment stage. Because, this research only to see the validity of the product. The instrument used was a validation sheet in the form of an assessment questionnaire by three validators. The data analysis technique used is Aiken V formula. The result validation of e-module an average of 0,83 with the valid category. From the validation results it can be said that Physics e-modul based on guided inquiry in- tegrated with ethnoscience to improve students creative thinking skills meets the valid criteria.